2020
DOI: 10.1038/s41598-020-76890-w
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum β-lactamase-producing Escherichia coli isolated from raw vegetables in South Korea

Abstract: The increasing prevalence of oxyimino-cephalosporin-resistant Enterobacteriaceae has become a global concern because of their clinical impact on both human and veterinary medicine. The present study determined the prevalence, antimicrobial susceptibility, and molecular genetic features of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (ESBL-EC) isolates from raw vegetables. A total of 1324 samples were collected from two agricultural wholesale markets in Incheon, South Korea in 2018. The ESBL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 63 publications
(64 reference statements)
2
22
1
Order By: Relevance
“…E. coli isolated from fresh vegetables showed resistance to cephalosporins, such CTX and CAZ (92%) ( Ye et al, 2018 ). In our study, E. coli was most frequently resistant to cephalosporins, such as CTX and CAZ (100%), and AMP (60%), which was not only consistent with the above reports for isolates from raw vegetables but also for isolates from clinical specimens (60%–62% to cephalosporins) and healthy subjects (72% to AMP) in low- and middle-income countries ( Nji et al, 2021 ; Teklu et al, 2019 ; Ye et al, 2018 ; Song et al, 2020 ). The resistance patterns of E. coli from different sources may be associated with each other because of transmission of resistance genes between humans and environments.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…E. coli isolated from fresh vegetables showed resistance to cephalosporins, such CTX and CAZ (92%) ( Ye et al, 2018 ). In our study, E. coli was most frequently resistant to cephalosporins, such as CTX and CAZ (100%), and AMP (60%), which was not only consistent with the above reports for isolates from raw vegetables but also for isolates from clinical specimens (60%–62% to cephalosporins) and healthy subjects (72% to AMP) in low- and middle-income countries ( Nji et al, 2021 ; Teklu et al, 2019 ; Ye et al, 2018 ; Song et al, 2020 ). The resistance patterns of E. coli from different sources may be associated with each other because of transmission of resistance genes between humans and environments.…”
Section: Discussionsupporting
confidence: 91%
“… Kim et al (2015) determined the antibiotic susceptibility of ESBL-producing E. coli and K. pneumoniae , isolated from sprout samples in South Korea, and showed these were resistant to CTX (100%). Another study showed that all ESBL-producing E. coli isolated from raw vegetables were completely resistant to AMP, CTX, and other antibiotics (piperacillin, cefazoline, and nalidixic acid) ( Song et al, 2020 ). E. coli isolated from fresh vegetables showed resistance to cephalosporins, such CTX and CAZ (92%) ( Ye et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…As previously suggested, all E. coli strains can be assigned to one of the seven well-recognized phylogenetic groups, namely A, B1, B2, C, D, E, and F, as previously suggested (Clermont et al, 2013). It has been reported that E. coli phylogenetic groups A and B1 are typically commensal strains, whereas the B2 and D groups are mainly urinary tract infection strains (Song et al, 2020). In this study, based on the phylogenetic analysis, we found that antibiotic resistance was associated with virulence among E. coli strains.…”
Section: Discussionsupporting
confidence: 52%
“…The isolates containing ST46, ST162, ST93 and ST58 were represented by one isolate each ( Figure 1 ). Recent reports documented that ST10 and ST224 E. coli are primarily carriers of CTX-M-15, CTX-M-14, CTX-M-1 and CTX-M-8 [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Our recent study identified ST8900 as the most prevalent ST (Sequence Typing) in CTX-M-27-positive E. coli isolates obtained during 2003 to 2009 [ 17 ].…”
Section: Resultsmentioning
confidence: 99%